Comprehensive HIRARC Implementation for Port Operations: A Multi-Zone Risk Management Framework - Nurprihatin, Filscha; Tampubolon, Faridah Hanum Br.; Ayu, Yayang Nadistya; Vaezi, Ali (Universitas Bunda Mulia, 2025)
Ensuring occupational safety in port operations is critical due to the inherently high-risk nature of maritime activities. This study presents an integrated application of the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) methodology across eight operational zones within a major container terminal. Using structured field observations, qualitative risk matrices, and industry-aligned compliance standards, hazards were systematically identified and categorized into low (5%), medium (87%), and high (8%) risk priorities. Key findings indicate recurrent hazards such as electrical shocks, slips, and container-handling incidents, with control strategies emphasizing administrative protocols, engineering measures, and personal protective equipment (PPE). The findings reaffirm that durable HIRARC implementation necessitates both engineering solutions and the active involvement of personnel, alongside an ongoing reinforcement of the safety culture. In this regard, the present study expands the occupational safety and health (OSH) knowledge by articulating a governance model for risk that is simultaneously generalizable and directly applicable to maritime terminals and comparably dense operational settings, effectively narrowing the distance between normative theory and tangible safety measures.